Mutation Profile of Resected EGFR‐Mutated Lung Adenocarcinoma by Next‐Generation Sequencing - Zhao, Ze‐Rui (Oncologist, 2019)
BACKGROUND. The efficacy of adjuvant targeted therapy for operable lung cancer is still under debate. Comprehensive genetic profiling is needed for detecting co‐mutations in resected epidermal growth factor receptor (EGFR)‐mutated lung adenocarcinoma (ADC), which may interfere the efficacy of adjuvant tyrosine kinase inhibitor (TKI) treatment. MATERIALS AND METHODS. Mutation profiling of 416 cancer‐relevant genes was conducted for 139 resected stage I–IIIa lung ADCs with EGFR mutations using targeted next‐generation sequencing. Co‐mutation profiles were systematically analyzed. RESULTS. Rare EGFR alterations other than exon 19 deletion and L858R, such as L861Q (∼3%) and G719A (∼2%), were identified at low frequencies. Approximately 10% of patients had mutations in EGFR exon 20 that could confer resistance to first‐generation TKIs. Ninety‐one percent of patients harbored at least one co‐mutation in addition to the major EGFR mutation. TP53 was the top mutated gene and was found more frequently mutated at later stage. Markedly, NF1 mutations were found only in stage II–III ADCs. Conversely, RB1 mutations were more frequent in stage I ADCs, whereas APC mutations were observed exclusively in this group. Thirty‐four percent of patients with EGFR TKI‐sensitizing mutations had genetic alterations involving EGFR downstream effectors or bypass pathways that could affect the response to EGFR TKIs, such as PIK3CA, BRCA1, and NOTCH1. CONCLUSION. Operable lung ADCs with EGFR TKI‐sensitizing mutations are associated with a high proportion of co‐mutations. Mutation profiling of these resected tumors could facilitate in determining the applicability and efficacy of adjuvant EGFR TKI therapeutic strategy. IMPLICATIONS FOR PRACTICE. The efficacy of adjuvant epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) therapy for lung cancer harboring EGFR mutation after surgical resection is still under debate. Next‐generation sequencing of 416 cancer‐relevant genes in 139 resected lung cancers revealed the co‐mutational landscape with background EGFR mutation. Notably, the study identified potential EGFR TKI‐resistant mutations in 34.71% of patients with a drug‐sensitizing EGFR mutation and who were naive in terms of targeted therapy. A comprehensive mutation profiling of these resected tumors could facilitate in determining the applicability and efficacy of adjuvant EGFR TKI therapeutic strategy for these patients.